Sustainable entrepreneurship : How entrepreneurs create value from sustainable opportunities - Masciarelli, Francesca; Leonelli, Simona (Bingley, U.K. : Emerald Publishing Limited, 2020)
Sustainable Entrepreneurship: How entrepreneurs create value from sustainable opportunities presents new frameworks to illustrate how entrepreneurs create value from sustainable opportunities and producing benefits for their business, society, and the environment. Employing research and analytical techniques from a wide variety of disciplines, including strategic management, regional studies, and innovation studies, Sustainable Entrepreneurship contributes to existing literature on this subject by delving deeply into the nature of sustainable entrepreneurial opportunities through the analysis of how contemporary wealth creators capitalize on those openings. Francesca Masciarelli and Simona Leonelli argue that entrepreneurship plays a crucial role in resolving ecological challenges through the creation of products, services and production methods that are simultaneously environmentally friendly and competitive on the market. This rigorous work offers unique new insights and represents a step towards the development of a more comprehensive analysis of sustainable entrepreneurship. By drawing on diverse perspectives, it demonstrates that the entrepreneur should consider the main sources of entrepreneurial opportunities and scrutinize the strategies and the local conditions that enable firms to create value.
Chapter 1: Understanding sustainable entrepreneurship -- Chapter 2: Suitability in the fashion industry -- Chapter 3: Who are sustainable entrepreneurs? -- Chapter 4: Implementing sustainable entrepreneurial opportunities through innovation -- Chapter 5: Local conditions for sustainable entrepreneurial opportunities.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Entrepreneurship; Business & Economics -- Entrepreneurship; Entrepreneurship